Thymidine Phosphorylase Expression and Microvascular Density Correlation Analysis in Canine Mammary Tumor: Possible Prognostic Factor in Breast Cancer - Nicola Zizzo; Giuseppe Passantino; Roberta Maria D'alessio; Roberta Maria D'alessio; Antonella Tinelli; Giuseppe Lopresti; Rosa Patruno; Domenico Tricarico; Fatima Maqoud; Rosa Scala; Francesco Alfredo Zito; Girolamo Ranieri (Frontiers in Veterinary Science, 2019)
Purpose: The thymidine phosphorylase (TP) is a key enzyme involved in the metabolism of pyrimidines. Inhibition or downregulation of this enzyme causes accumulation of metabolites with consequences in DNA replication. TP regulates angiogenesis and chemotactic activity of endothelial cells. Different studies showed the presence of TP upregulation in human cancer but the correlation between TP expression and the microvascular density (MVD) in canine mammary tumors is unknown. The aim of this study was to investigate a possible correlation between the MVD and TP expression in tumor cells of canine mammary tumors of different degree of severity (G1–G3) by immunohistochemical analysis.Methods: Sixty-eight samples of spontaneous mammary neoplasia of 5–12 cm in diameter were collected from purebred and mixed-breed dogs (mean aged = 9.5 ± 7), not subject to chemotherapy treatments in veterinary clinics. Histopathological analysis and immunostaining were performed.Results: Carcinoma simple samples have been classified as 72.06% of tubule-papillary, 20.59% cysto-papillary, and 7.35% tubular carcinomas. Immunostainings revealed a marked cytoplasmic expression of TP in 30.88% of samples, mild in 32.35%, weaker in 22.07%, and negative in 14.70%. The correlation analysis and two-way ANOVA showed a linear correlation between MVD and TP with a coefficient of correlation (r) > 0.5 (p < 0.05) in G2 and G3. No correlation between variables was found in G1.Conclusions: These findings suggest that cytoplasmic TP overexpression is correlated with microvascular density in canine mammary tumors, in severe grade, and it can be a potential prognostic factor in breast cancer.